A DESMOID TUMOR IN PREGNANCY MIMICKING SUBCUTANEOUS ENDOMETRIOSIS; A CASE REPORT - Arif Aktuğ Ertekin; Ebru Çöğendez; Erhan Uncu; Erbil Çakar; Nazan Tarhan; Habibe Ayvacı (İstanbul Tıp Fakültesi Dergisi)
Desmoid tumors are benign non-metastasizing tumors. However, they may proliferate and infiltrate into adjacent tissues with high recurrence rates. Even though its etiology is unclear, a previous histories of trauma, surgery, pregnancy, use of medication containing estrogen, and having conditions such as familial adenomatous polyposis and Gardner syndrome can be regarded as contributing or risk factors.